Fischer indolisation of N-(α-ketoacyl)anthranilic acids into 2-(indol-2-carboxamido)benzoic acids and 2-indolyl-3,1-benzoxazin-4-ones and their NMR study - Proisl, Karel; Kafka, Stanislav; Urankar, Damijana; Gazvoda, Martin; Kimmel, Roman; Košmrlj, Janez (Organic & biomolecular chemistry, 2014)
N-(α-ketoacyl)anthranilic acids reacted with phenylhydrazinium chloride in boiling acetic acid to afford 2-(indol-2-carboxamido)benzoic acids in good to excellent yields and 2-indolyl-3,1-benzoxazin-4-ones as by-products. The formation of the latter products could easily be suppressed by a hydrolytic workup. Alternatively, by increasing the reaction temperature and/or time, 2-indolyl-3,1-benzoxazin-4-ones can be obtained exclusively. Optimisations of the reaction conditions as well as the scope and the course of the transformations were investigated. The products were characterized by (1)H, (13)C and (15)N NMR spectroscopy. The corresponding resonances were assigned on the basis of the standard 1D and gradient selected 2D NMR experiments ((1)H-(1)H gs-COSY, (1)H-(13)C gs-HSQC, (1)H-(13)C gs-HMBC) with (1)H-(15)N gs-HMBC as a practical tool to determine (15)N NMR chemical shifts at the natural abundance level of (15)N isotope.
Keywords: ortho-Aminobenzoates; Indoles; Benzoxazines; magnetická rezonanční spektroskopie; indoly; Magnetic Resonance Spectroscopy; benzoxaziny; benzoáty; Benzoates; ortoaminobenzoáty